PEREBUTAN DESA: TINJAUAN PEMILIHAN KEPALA DESA SERENTAK DI KABUPATEN HALMAHERA UTARA TAHUN 2018 - Simson Tondo (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2019)
The main objective of this paper is to see the struggle of village leaders since the birth of law number 6 of 2014 concerning Villages with a description of the phenomenon of simultaneous village head removal in the northern Halamhera district in 2018. The birth of the village law made the village position shift from the administrative area in Under the regency and sub-district becomes the right to regulate and manage self-government affairs with its privileges to provide recognition and respect for existing villages with their diversity before and after the formation of the Unitary State of the Republic of Indonesia, strengthening village communities as the subject of development known as Village Development means participating in planning and decision making and Village Building means as the main actor (subject) who plans, finances and implements it. The phenomenon of seizure of power in the village also occurred in North Halmahera through the Village Head Election  simultaneously in 2018, the number of participants participating in the village head electoral competition reached 8 to 9 people / village, in addition academics with Doctoral degrees also participated in taking leadership village. The research method used is a qualitative method.